Hubungan Perilaku Caring Perawat dengan Pemenuhan ADL (Activities of Daily Living) Pasien di Ruang Penyakit dalam RSUD dr. Doris Sylvanus Palangka Raya - Retno Widhiasih; Dwi Agustian Faruk Ibrahim; Ayu Puspita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Nurses need to be caring to be responsive and care about patient needs. One of the patient's needs that must be met is ADL needs including bathing, dressing, going to the bathroom, moving/mobility, defecation/defecation and food. Nurses are less concerned about fulfilling daily ADLs such as assisting with patient mobility, not facilitating bowel movements, and paying less attention to patient hygiene even though patients need the presence of a nurse. Aims to determine the relationship between nurses' caring behavior and patient ADL fulfillment in the internal medicine ward at Dr. RSUD. Doris Sylvanus Palangka Raya. The research design used is correlation with a cross sectional method which aims to determine the correlative relationship between two variables. The instruments used were questionnaires and Chi-Square statistical tests aimed at patients in the Internal Medicine Room with a total of 37 patients. Results of the significance value of the relationship between nurses' caring behavior and patient ADL fulfillment in the internal medicine ward at RSUD dr. Doris Sylvanus Palangka Raya is 0.000 < 0.05. So Ha's hypothesis is accepted, which means that there is a relationship between nurses' caring behavior and the patient's ADL fulfillment in the internal medicine ward at dr. RSUD. Doris Sylvanus Palangka Raya. There is a correlation between nurses' caring behavior and patients' ADL fulfillment in the internal medicine ward at dr. Doris Sylvanus Palangka Raya Hospital. Based on the results of this research, it is hoped that nurses will increase caring behavior in providing nursing services so that the quality of nursing care will be good.